HIGH FREQUENCY CONVERTER FOR INDUCTION HEATING APPLICATION - Prof. Shaikh A. H. A. R.; Mr. Dhayagonde Sachin Basappa; Mr. Jadhav Rajat Ramesh; Mr. Ohol Harish Dadasaheb (International Journal of Innovations in Engineering Research and Technology, 2023)
The proposed topology reduces the harmonic distortion of high frequency AC/AC converter well below the acceptable limit. This project deals with a novel single phase AC/AC soft switching utility frequency AC to high frequency AC converter. A combination of R-L-C circuit along with the MOSFET is used in front end for converting utility frequency instead of conventional diode bridge rectifier to provide continuous sinusoidal input with nearly unity power factor at source side. This power converter is more suitable and acceptable for cost effective high frequency (HF) consumer induction heating application. A contactless power transfer system has many advantages over conventional power transmission due to the elimination of direct electrical contacts with the development of modern technologies. IPT (Inductive Power Transfer) has become a very attractive technology for achieving wireless/contactless power transfer over the past decade and has been successfully employed in many applications, such as materials handling, lighting, transportation, bio-medical implants, etc.